Alarming call from Mursala Island, North Sumatra, Indonesia: The urgent task of conserving the previously reported extinct of Dipterocarpus cinereus - HENTI HENDALASTUTI RACHMAT; ATOK SUBIAKTO; KESUMA WIJAYA; ARIDA SUSILOWATI (Society for Indonesian Biodiversity, 2018)
Rachmat HH, Subiakto A, Wijaya K, Susilowati A. 2018. Alarming call from Mursala Island, North Sumatra, Indonesia: The urgent task for conserving the previously reported extinct of Dipterocarpus cinereus. Biodiversitas 19: 399-405. IUCN Red List (1998) declared that the Mursalan endemic Dipterocarpus cinereus was extinct in the wild, but brief exploration conducted in the first quarter of 2013 found that there were few numbers of D. cinereus still growing in the island. The objectives of this research were: to describe the current condition of the forest in Mursala island; and to determine the vegetation composition and association between D. cinereus and other major tree species in site. Identifying forest condition and the potential value of the non-timber product was done descriptively through direct observation and interview with local inhabitants. The vegetation analysis was carried out by a purposive stratified technique in three lines each consisting of 4-8 plots (quadrats). The size of each sampling plot was 1,000 m2 (r= 17.8 m) with the total of 20 plots. The result showed that D. cinereus is still growing in the middle part until the top of the ridges. Importance Value Index (IVI) for the top five species were 32.37, 39.47, 17.43, 15.18 and 11.04 respectively for D. cinereus, Shorea acuminata, Arenga pinnata, Shorea falcifera and Hopea sangal. Among those five dominant species, only D. cinereus with S. falcifera and D. cinereus with A. pinnata had a significant association. Our study also determined that calling for species conservation is alarming rate and those not only needed for D. cinereus alone but island ecosystem as a whole.